Study of Tourists Movement Pattern in Coastal Area and Small Islands, Makassar City - Sri Aliah Ekawati; Stevanny Manga; Fitha Rachma Sari; Febrika Rahmaniah Nurul (Ruang, 2021)
Makassar City is one of the coastal cities in Indonesia which has various tourist attractions. This tourist attraction is one of the interesting things considered by the people of Indonesia and even the world to visit Makassar City. This study aims to identify patterns of tourist movement in several coastal tourism areas and small islands in Makassar City. The method used in this research is qualitative method. Data obtained by searching secondary data, observation and distributing questionnaires online. Spatial analysis is done by interpreting the image map and digitizing it with ArcGIS, then analyzing the description. Through this research, it is known that there are three patterns of tourist movement, namely single point, base site and stop over. Based on these results, it is directed to develop a one day trip tourism concept.